Expression of CTGF and Cyr61 in colorectal cancer. Issue 1 (15th November 2010) - Ladwa, Rahul; Pringle, Howard; Kumar, Rohan; West, Kevin
Abstract : Background: The CCN genes encode secreted extracellular matrix proteins cysteine rich-61 (Cyr61), connective tissue growth factor (CTGF) and nephroblastoma overexpressed (Nov). They are involved in diverse cellular functions. Expression of these factors in tumours has produced conflicting results. More recently, research has focused on molecular biomarkers to indicate progression of a disease or the susceptibility of the disease to a given treatment. Aims: The purpose of this study was to determine the expression of CTGF and Cyr61 genes and proteins in colorectal cancer. Expression was compared with various clinicopathological parameters including Dukes' stage and TNM stage. We determined the in vitro effects of hypoxia on Cyr61 and CTGF expression in colorectal cancer cell lines. Results: Hypoxia significantly reduced CTGF mRNA expression (p<0.01) in HT29 and Caco-2 cell lines. Cyr61 was induced (p<0.01) in HT29 cell lines but significantly reduced (p<0.01) in Caco-2 cell lines under hypoxic conditions. High levels of CTGF and Cyr61 mRNA were found in colorectal cancer compared with normal colon (p<0.05). Expression was reduced in more advanced cancers (Dukes' C vs Dukes' A and B). There was a significant association between CTGF protein expression and advancing Dukes' stage (p<0.01), T stage (p<0.01) and lymph-node involvement (p<0.05), but there was no significant association between Cyr61 expression and clinicopathological parameters. Conclusion: Upregulation of Cyr61 and CTGF gene expression in colorectal cancer suggests they have a role in tumour initiation or development. However, the genes are not as highly expressed in advanced stages of colorectal cancer, suggesting their role may be important at an early stage of tumour development. These genes maybe used as early biomarkers to risk-stratify patients. Hypoxia alters the expression of these genes in colorectal cancer cell lines. Further studies are needed to determine whether targeting these genes would be useful in future therapy.